Needs Assessment of ICT Users for Implementation of Aquacultural Development Projects in Coastal Areas - P., Mahalakshmi; M., Krishnan; D., Deboral Vimala; T., Ravisankar (Fishery Technology, 2025)
An information and training needs assessment of users of Village Resource Centre (VRC) and Village Knowledge Centres (VKCs) of Thangatchimadam, Ramanathapuram district, Tamil Nadu was conducted. The opinions of 103 users of VKCs on information and training needs dimensions such as culture practices, e-Leaming module, extension activities, fisheries and allied information and base information have been investigated by means of a survey questionnaire. The need for culture practices in lobsters, information on soil and water management in shrimp culture in the form of e-Leaming module, training and marketing information in value added products, preparation of quality and hygienic dry fish, addresses of various fisheries and aquaculture departments and universities, and information on subsidies for fishermen, aqua farmers and women were the information sought by the VKCs for adoption of aquaculture in coastal areas. Rank order correlation coefficients were worked out to compare the information and training needs among the users of various VKCs. The results indicated that almost similar ranks were assigned to various information and training needs by VKCs users.